Fatty acid and phytosterol content of commercial saw palmetto supplements - Penugonda, Kavitha; Lindshield, Brian L. (My University, 2013)
Saw palmetto supplements are one of the most commonly consumed supplements by men with prostate cancer and/or benign prostatic hyperplasia (BPH). Some studies have found significant improvements in BPH and lower urinary tract symptoms (LUTS) with saw palmetto supplementation, whereas others found no benefits. The variation in the efficacy in these trials may be a result of differences in the putative active components, fatty acids and phytosterols, of the saw palmetto supplements. To this end, we quantified the major fatty acids (laurate, myristate, palmitate, stearate, oleate, linoleate) and phytosterols (campesterol, stigmasterol, β-sitosterol) in 20 commercially available saw palmetto supplements using GC-FID and GC-MS, respectively. Samples were classified into liquids, powders, dried berries, and tinctures. Liquid saw palmetto supplements contained significantly higher (p < 0.05) concentrations of total fatty acids (908.5 mg/g), individual fatty acids, total phytosterols (2.04 mg/g), and individual phytosterols, than the other supplement categories. Powders contained significantly higher (p < 0.05) concentrations of total fatty acids than tinctures, which contain negligible amounts of fatty acids (46.3 mg/g) and phytosterols (0.10 mg/g). Our findings suggest that liquid saw palmetto supplements may be the best choice for individuals who want to take a saw palmetto supplement with the highest concentrations of both fatty acids and phytosterols.
Keywords: Saw palmetto; Serenoa repens; Prostate; Benign prostatic hyperplasia; Prostate cancer; Fatty acids; Phytosterols; Supplements